Solid self-emulsifying drug delivery system of domperidone for improved biopharmaceutical characteristics - Chowdhury, Saadia Shams (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.